Topical application of silver-curcumin on wound healing in rabbits (Bangladesh Veterinarian, 2016)
Curcumin, a natural product obtained from the rhizomes of Curcuma longa, is used traditionally in prevention of wound infection. To determine the effects of silver and curcumin combination on surgical wound healing, a study was conducted in rabbits. A total of 32 surgical wounds were created in 16 rabbits in four groups. Information was recorded from Day 0 to Day 42 postoperatively. Swelling area of wound, elevation of suture line from the skin surface, width of sutured area and contraction length were recorded weekly. Treatment with curcumin, 1% silver sulfadiazine (1% SSD) and a mixture of the two resulted in swelling of 11.4 ± 0.1 mm, 11.1 ± 0.4 mm and 11.0 ± 0.1 mm, respectively. Swelling (12.2 ± 0.3mm) and elevation of sutured line was higher (3.4 ± 0.2 mm) in wounds of control group and lower (2.3 ± 0.1 mm) in wounds treated with a mixture of curcumin and 1% SSD. The scores of wound colonization were lowest (0.8) in 1% SSD group followed by mixture of curcumin and 1% SSD (1.0), curcumin (1.3) and tincture of benzoin (1.6) alone. Histopathologically reactive cells decreased markedly in wounds treated with combination of 1% SSD and curcumin at D3 with increased fibrous connective tissue. However, wounds treated with 1% SSD showed fewer reactive cells than curcumin group. Proliferation of fibrous connective tissue was highest in the silver treated wound, which indicates good wound healing process. Overall, wound healing was improved by the topical application of 1% SSD alone. Curcumin had positive effects on wound healing process but less than 1% SSD. These results indicate that 1% silver sulfadiazine is the best topical therapy for wound management in rabbits.Bangl. vet. 2015. Vol. 32, No. 2, 55-64